2020
DOI: 10.1111/ijfs.14650
|View full text |Cite
|
Sign up to set email alerts
|

A synbiotic marine oligosaccharide microcapsules for enhancing Bifidobacterium longum survivability and regulatory on intestinal probiotics

Abstract: A novel synbiotic multiparticulate microparticle containing alginate oligosaccharide (AOS), chitosan oligosaccharide (COS) and Bifidobacterium longum CICC 6259 was produced in the current study to expand the synbiotic industrial applications. The influences of these treatments on encapsulation yield, size, morphology, protective effect and stability of microcapsules and on mice gut microbiome were studied in vitro and in vivo. In vitro experiments detected no significant difference (P > 0.05) in encapsulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Another example of the modulatory effect of microencapsulated probiotics is the study carried out by Chang et al , 66 where Bifidobacterium longum was co-encapsulated with a marine oligosaccharide and administered to a group of mice after proving in vitro that the probiotic survives in an adequate concentration in gastrointestinal conditions. When administered to mice, these microcapsules significantly increased the content of Bifidobacterium and Lactobacillus and reduced the content of Enterococcus and Escherichia in the gut microbiome of the mice.…”
Section: Effect Of Encapsulated Compounds and Probiotics On The Gut M...mentioning
confidence: 99%
See 1 more Smart Citation
“…Another example of the modulatory effect of microencapsulated probiotics is the study carried out by Chang et al , 66 where Bifidobacterium longum was co-encapsulated with a marine oligosaccharide and administered to a group of mice after proving in vitro that the probiotic survives in an adequate concentration in gastrointestinal conditions. When administered to mice, these microcapsules significantly increased the content of Bifidobacterium and Lactobacillus and reduced the content of Enterococcus and Escherichia in the gut microbiome of the mice.…”
Section: Effect Of Encapsulated Compounds and Probiotics On The Gut M...mentioning
confidence: 99%
“…43,45 Also, microparticles encapsulating LGG by freeze drying allowed the probiotic to survive in an adequate concentration to colonize the colon; this was proved by the results obtained for the microbial community structure, which showed that LGG outcompeted other species of lactobacilli. 69 Another example of the modulatory effect of microencapsulated probiotics is the study carried out by Chang et al, 66 where Bifidobacterium longum was co-encapsulated with a marine oligosaccharide and administered to a group of mice after proving in vitro that the probiotic survives in an adequate concentration in gastrointestinal conditions. When administered to mice, these microcapsules significantly increased the content of Bifidobacterium and Lactobacillus and reduced the content of Enterococcus and Escherichia in the gut microbiome of the mice.…”
Section: Food and Function Reviewmentioning
confidence: 99%
“…Charged interactions ensure a secure and even coating, even when common materials are used such as alginate and chitosan. [66,[85][86][87] An example of this was the emulsification of free cells (B. longum) in an alginate hydrogel that were dip-coated in a chitosan solution. [70] This 36 μm coating slightly decreased the encapsulation yield, but dramatically increased survivability in simulated gastric fluid (SGF) (pH 2.5) and simulated intestinal fluid (SIF) with bile salts (pH 6.8).…”
Section: Single Component Core + Single Component Shellmentioning
confidence: 99%
“…However, regulating the processing of synbiotic products from the beginning of production to the end of the shelf life is needed for preserving consumer acceptance. For this purpose, several techniques can be used which primarily include fortifying the product with prebiotics and adding probiotic microcapsules (Dias et al, 2018;Chan et al, 2020).…”
Section: Challenges In Non-dairy Synbiotic Industrymentioning
confidence: 99%